PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV - Harahap, Nikmal Luthfi; Unita, Imelda Free Unita; Perangin-angin, Laurensia Masri Perangin angin; Ananda, Lala Jelita Ananda; Nasution, Yusra Nasution; Perangin-angin, Laurensia Masri Perangin-angin (Jurnal Merah Putih Sekolah Dasar, 2025)
This research is based on the low achievement of fourth-grade students in social studies, which have not yet met the established Minimum Completion Criteria. This is due to the teacher-centered learning process, which uses conventional teaching methods. This learning process does not optimally encourage student activity and engagement, creating a monotonous learning environment that results in low student motivation and enthusiasm for learning. This study used the CORE (Connecting, Organizing, Reflecting, Extending) learning model, which emphasizes student-centered learning, where students connect, organize, rethink, and expand their understanding of the learning material. This study employed a nonequivalent control group design with a sample of 72 students (36 students in the control class and 36 students in the experimental class). The research instrument was a multiple-choice test that had been piloted. The data were analyzed using descriptive and inferential statistics. The results indicate that the CORE (connecting, organizing, reflecting, and extending) learning model significantly influences the science learning outcomes of fourth-grade students at MIN 1 Padangsidempuan. This is demonstrated by the hypothesis test calculation using a paired sample t-test, which showed a value of 0.000 < 0.05, thus rejecting H0 and accepting Ha.